The replication and titration of iridescent virus type 22 in Spodoptera frugiperda cells - Brown, D A; Lescott, T; Harrap, K A; Kelly, D C (Journal of general virology, 1978)
A plaque assay for iridescent virus type 22 (from Simulium sp.) using Spodoptera frugiperda cells has been devised, and the kinetics of growth of the virus in this cell line have been determined. The virus particle/p.f.u. ratio was 75 +/- 8, and the p.f.u./TCID50 ratio was 0.56 +/- 0.11.